Ideologi Surat Kabar dalam Pemberitaan Terorisme - Fajar Syuderajat (Communicatus: Jurnal Ilmu komunikasi, 2017)
This paper this study was to determine the ideology of Newspaper Coverage Off Execution Amrozy Cs. on Newspaper Kompas and Republika. The method used in this research is the analysis method semiotics model of Ferdinand de Saussure with a qualitative approach. The results showed that: (a) Option speech text, as well as the news angle images of photographs or illustrations that reproduce the graph becomes a news event is strongly influenced by the ideology of the media is concerned. (B) Compass showing partiality to the international agenda by using the term "terrorists" in its message. This is also strengthened by the news in the form of photo illustrations which only includes figures or portraits of security officers. (C) Republika has a distinctive news angle in reporting the death penaltyÂ  convicted Bali Bombing Case. They appear at the peculiarities of the text selection, angle coverage, as well as news illustrations are photographs which contains many figures or portraits Amrozi.